Study of the Effects of Visual, Auditory and Kinesthetic Learning Styles on Memory of Learning Materials - Karten Halirat; Mukh Khusnaini; Hizkia Gymnastic Mautang; Chrismanto Purba; Moh. Erwin Budiana (CV. Get Press Indonesia, 2025)
The evolving educational landscape demands effective pedagogical strategies addressing diverse student needs. Learning styles, particularly the Visual, Auditory, and Kinesthetic (VAK) framework, have gained prominence for their recognized impact on comprehension and retention (Rao et al., 2022). Despite established links between VAK alignment and general academic achievement (Maulina et al., 2021), a specific gap remains in understanding how each VAK style uniquely influences long-term memory of academic content. This study aimed to quantitatively analyze the effect of VAK learning styles on students' memory of academic content using an existing secondary dataset. Utilizing an open-access dataset ( secondary school students) collected during 2021–2025, the research focused on pre-recorded VAK classifications and standardized memory scores. Statistical analysis, employing ANOVA and Tukey HSD post-hoc tests (IBM SPSS Statistics 28), was performed. Results showed a significant difference in memory scores across VAK groups, , , with a partial eta squared . Auditory learners exhibited higher retention () compared to Visual () and Kinesthetic () learners, with significant pairwise differences (). These findings underscore learning style as a critical predictor of memory capacity, advocating for differentiated and multimodal pedagogical approaches to optimize student learning. Future research should investigate moderating variables and develop adaptive assessment systems.